Suŝestvuet li ritorika naučnogo diskursa? - Lassan, Èleonora R. (Stylistyka, 2019)
The article focuses on the phenomenon of the contemporary academie discourse and námely on those processes that lead to its becoming senseless, as the author suggests. It happens as a resull of the unifícation of the formulas of the academie discourse, which are accepted as rituál ones in the academie community. Since the consciousness that seeks to aware is hidden behind the forms that are above individual, it, on the one hand, dechneš the responsibility for the mechanisms of the paradigm chosen in the research, and, on the other hand - communicates the academie elites, dictating “the rules of the game”, about the academie loyalty of the former. In thus sense the comparison of the contemporary academie rhetoric, as a systém of the means to get adapted to the existing demands, to the rhetoric of totalitarian discourses suggests itself: in both cases the consciousness that is behind the text does not allow oneself to stand out as individuality but, on the contrary, demonstrates its submission to the existing rules, or in other words, to the loyalty demanded by the community.